Colour Alone. The Chromatic Hues of The Concepts of “Painterly” and “Post Painterly” in Clement Greenberg’s Aesthetics (Itinera, 2020)
This essay aims to analyse the importance of colour in Clement Geenberg’s theory of art, and its relevance on modernist ontology of pictorial image. It focuses in particular on the shift from the notion of “painterly” to the notion of “post painterly” in the greenbergian aesthetic vision of painting. Firstly, it deals with a recollection of Greenberg’s appropriation of the very concept of “painterly” from Heinrich Wölfflin’s Principles of Art History. Then, it provides an articulated explanation of Greenberg’s arguments on “painterly” and “post painterly”, in respect of their implications with pure colour. Finally, it stresses Greenberg’s troublesome concern with objecthood in art, referring the problematic threshold between monochromatic painting, blank canvases as works of art and a “non painterly” perspective on pictorial images.